A CubeSAT payload for in-situ monitoring of pentacene degradation due to atomic oxygen etching in LEO. (September 2016) - Gorreta, Sergi; Pons-Nin, Joan; López, Gema; Figueras, Eduard; Jové-Casulleras, Roger; Araguz, Carles; Via, Pol; Camps, Adriano; Domínguez-Pumar, Manuel
Abstract: This paper reports and discusses the design and ground tests of a CubeSat payload which allows to measure, in-situ and in real time, the degradation of a polymer of electronic interest due to atomic oxygen etching in LEO. It provides real-time information on how the degradation occurs, eliminating the need to work with samples recovered once the mission has finished. The polymer, TIPS-Pentacene, is deposited on the surface of a microelectromechanical (MEMS) cantilever, which works as a resonator embedded in a Pulsed Digital Oscillator circuit. The mass losses in the polymer due to atomic oxygen corrosion produce variations in the resonant frequency of the MEMS, which is continuously sensed by the circuit and transmitted to the ground. This way, polymer mass losses around 10 −12  kg can be detected during the mission. The payload is a part of the 3 Cat-1 mission, a nano-satellite aimed at carrying out several scientific experiments. Abstract : Highlights: New CubeSat payload to in-situ sense pentacene degradation due to ATOX erosion in LEO. Sensing strategy is mass loss detection, using a MEMS resonator. Different mechanical vibration modes of the MEMS are used. Data is sent to the ground in real-time during the mission. Ground tests indicate that mass losses around 1e-12 kg can be detected.